Robust natural organic matter removal from Scottish water sources of variable DOC content. - Golea, Dan-Mihai (Cranfield University, 2019)
Natural organic matter (NOM) is found ubiquitously in raw water and is known to react with the chlorine used in water treatment to produce disinfection by-products (DBPs), some of which are potentially harmful to human health due to their links with cancers. Trihalomethanes (THMs) and haloacetic (HAAs) acids are the two types of carbonaceous DBPs widely regulated. The THMs and HAAs are widely regarded as being good indicators of the presence of the more than 500 other DBPs that have been found in treated drinking water. At large and medium sites in Scotland, the coagulation- flocculation process has long been the main control barrier for removal of the precursors for DBPs. At small sites, ultra and nano filtration membrane filtration processes have been considered a good solution due to their small footprint requirement and large volume of water output. In addition, granular activated carbon (GAC) filtration has long been employed for removal of organic matter. However, increases in the organic content of raw waters, stricter regulatory requirements and concerns over coagulant cost and availability have driven the reconsideration of how NOM laden water sources in Scotland are treated. This thesis investigated the approaches required to increase the robustness of drinking water supply to mitigate against these factors. A stronger correlation was found between commonly measured water quality parameters and DBPs in raw water sources compared to treated water, which was as a result of the lower hydrophobic content of the latter. However, the DBP removal as a function of DOC reduction was calculated and revealed coagulation using ferric sulfate in the pH 4-5-5-5 range as the most feasible solution at large and medium sites. The use of GAC media with high pore uniformity would be appropriate at large or medium sited where up to 50% DOC reduction would be sufficient to control DBPs. At small sites, the tighter pore size membranes showed improved THM precursor removal, whilst most of these maintained a throughput of within 90% of the current membranes.
Keywords: Natural organic matter; disinfection by-products; coagulation; spiral wound membranes; granular activated carbon; hydrophobic content